An effector protein of the wheat stripe rust fungus targets chloroplasts and suppresses chloroplast function - Xu, Qiang; Tang, Chunlei; Wang, Xiaodong; Sun, Shutian; Zhao, Jinren; Kang, Zhensheng; Wang, Xiaojie (Nature communications, 2019)
Chloroplasts are important for photosynthesis and for plant immunity against microbial pathogens. Here we identify a haustorium-specific protein (Pst_12806) from the wheat stripe rust fungus, Puccinia striiformis f. sp. tritici ( Pst ), that is translocated into chloroplasts and affects chloroplast function. Transient expression of Pst_12806 inhibits BAX-induced cell death in tobacco plants and reduces Pseudomonas -induced hypersensitive response in wheat. It suppresses plant basal immunity by reducing callose deposition and the expression of defense-related genes. Pst_12806 is upregulated during infection, and its knockdown (by host-induced gene silencing) reduces Pst growth and development, likely due to increased ROS accumulation. Pst_12806 interacts with the C-terminal Rieske domain of the wheat TaISP protein (a putative component of the cytochrome b6-f complex). Expression of Pst_12806 in plants reduces electron transport rate, photosynthesis, and production of chloroplast-derived ROS. Silencing TaISP by virus-induced gene silencing in a susceptible wheat cultivar reduces fungal growth and uredinium development, suggesting an increase in resistance against Pst infection. Chloroplasts are important for plant immunity against microbial pathogens. Here Xu et al. identify, in the wheat stripe rust fungus, a haustorium-specific protein that is translocated into chloroplasts and affects chloroplast function by interacting with a putative component of the plant cytochrome b6-f complex.